Analysis of Income and Feasibility of Refill Drinking Water Depot Business in North Tatura Sub-District, Palu City - Yusril, Moh.; Jaya, Andi Herman; HM, Syamsuddin; Yunus, Rita; Yunus, Santi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
This research aims to analyze the income level and business feasibility of refillable drinking water depots in Tatura Utara Subdistrict, Palu City. A descriptive approach was applied, with data collected through interviews, questionnaires, and documentation involving five business units that have been operating for at least three years. The results show that the average monthly production cost is IDR 5,088,794, while the average monthly revenue reaches IDR 11,030,000, resulting in an average net income of IDR 5,941,205 per business unit. The R/C ratio obtained is 2.16, indicating that everyone rupiah spent generates IDR 2.16 in revenue, which reflects high economic efficiency. In addition, the average Break Even Point is 282 gallons per month, demonstrating that all business units have surpassed the break-even threshold. These findings conclude that refillable drinking water depots in the area offer a viable and sustainable business opportunity in urban environments.